The Influence of eWOM and Customer Satisfaction on Purchasing Decisions - Fahma Rindha Purba; Eristia Lidia Paramita (International Journal of Social Science and Business, 2021)
The current development of technology makes it easier for humans to search for information. Electronic words of mouth (eWOM) or information media through the internet becomes the most widely used media by the public to search for needs, dig information, evaluate alternatives, and make purchasing decisions. After recognizing the needs, the public starts looking for information about the products they need to purchase. The better the review provided by someone, the higher the purchasing interest. This study aims to analyze the effect of eWOM and customer satisfaction on purchasing decisions. This study uses quantitative methods. It involved 132 customers aged 18-60 years old who have purchased Argotelo products as samples. The sample was determined using a purposive sampling technique. The data were analyzed using multiple linear regression. The results of the analysis showed that eWOM affects purchasing decisions. Then, customer satisfaction affects purchasing decisions. Besides, eWOM and customer satisfaction affect purchasing decisions.